Experiment on superadiabatic radiant burner with augmented preheating. (15th October 2015) - Wu, H.; Kim, Y.J.; Vandadi, V.; Park, C.; Kaviany, M.; Kwon, O.C.
Highlights: Potential of superadiabatic radiant burners (SRBs) is experimentally confirmed. The SRB consists of two-layered porous media, a preheater and radiation rods. The SRB can be operated at very fuel-lean condition due to enhanced heat recovery. CO/NOx emissions are reduced compared with the conventional porous radiant burners. The SRB is acceptable for practical applications. Abstract: A radiant porous burner with augmented preheating (i.e., superadiabatic radiant burner, SRB) is experimentally investigated. The porous alumina (Al2 O3 ) burner with a square cross-section consists of a small-pored upstream section for internally preheating the incoming gas mixture, a large-pored downstream section for establishing flame, a preheater for externally recovering heat from the exiting flue gas and preheating the inlet air for the burner in addition to the internal heat recirculation in the small-pored upstream section, and radiation corridors for extracting heat from the flame and transferring it to radiating disk surfaces. Temperature distribution and combustion stability limits of flame in the SRB and the nitrogen oxide (NOx ) and carbon monoxide (CO) emissions are measured. Results show that the SRB can be operated even at very fuel-lean condition because of the internal and external heat recirculation, showing blow-off and flash-back limits for a given fuel-equivalence ratio. It is observed that the superadiabatic radiation temperature on the disk surfaces is higher than the flue gas temperature at the same axial location, experimentally confirming the previous theoretical and computational results of SRBs. Improved performance of CO and NOx emissions compared with the conventional porous radiant burners also indicates that the SRB is acceptable for practical application.